HUBUNGAN POLA KONSUMSI MAKANAN DAN AKTIVITAS FISIK DENGAN STATUS GIZI PADA MAHASISWA SARJANA DI UNIVERSITAS SEBELAS MARET - Reny Rahmawati; Abdul Fandi; Husnul Khatimah; Juwitriani Alwi; Nyono Dedi Prabowo; Meintansari Manik (Poltekkes Kemenkes Medan, 2025)
University students are a population vulnerable to dietary pattern shifts and reduced physical activity due to academic demands and lifestyle changes. These factors may contribute to both undernutrition and overnutrition. Objective: This study aimed to analyze the association between dietary habits, physical activity, and nutritional status among undergraduate students at Universitas Sebelas Maret. A cross-sectional observational study was conducted involving 150 students selected via simple random sampling from five faculties. Validated questionnaires assessed snacking frequency, late-night eating habits, and physical activity. Nutritional status was determined using Body Mass Index (BMI). Data were analyzed using Chi-square tests. Significant associations were found between nutritional status and snacking frequency (p = 0.000), late-night eating (p = 0.046), and physical activity frequency (p = 0.028). Students who frequently snacked, consumed meals late at night, and engaged in low physical activity tended to exhibit overweight or obesity.Unhealthy dietary behaviors and insufficient physical activity are significantly associated with increased nutritional status among university students. Targeted health promotion and preventive interventions are essential to foster healthier lifestyles in this population.